(untitled) (International Journal of Engineering Sciences & Management Research, 2016)
In today’s era the main concern of technocrats is to find out the efficient storage space for users. So that they can store any kind or any size of data their without spending lots of money on storage devices. The birth of ‘cloud’ technology is just like boon for users. Anywhere and anytime usage of cloud services are quite beneficial for their users. Various cloud services like SAAS, PAAS, IAAS, DBAAS are taken on rent by the users for their own usage. CloudAnalyst tool based on cloudsim is used for storing data on different data centers. It also worked as a load balancer for datacenters so that load can be equally spread on every datacenters. This survey paper focused on various algorithms which are used for spreading load equally on datacenters so that no datacenter is suffering from the problem of overloading. The comparative performance analysis of such algorithms is also taken into account.